The population density of Digitaria insularis influences Phaseolus vulgaris agronomic traits - Tomazini, Jovani (2022)
The common bean (Phaseolus vulgaris L.) is an important species for human nutrition in Brazil and its cultivation has been hampered in recent years by the interference of sourgrass [Digitaria insularis (L.) Mez ex Ekman] populations. However, just a few studies evaluated sourgrass interaction with common beans. Therefore, we aimed to evaluate the influence of sourgrass density on common bean agronomic characteristics. Seven sourgrass densities, equivalent to populations from 0 to 12 plants m-², were established in a common bean crop field with a randomized block design and four replicates. The increase in sourgrass density boosted weed dry matter and the common bean plant’s height and leaf area index. Contrarily, the same increase in weed density reduced the crop chlorophyll content, stem diameter, shoot, root and total dry mass, and grain yield. The variables’ behavior testifies to the high sensitivity of the common bean to sourgrass interference reported by farmers. Variables such as common bean chlorophyll, stem diameter, and the shoot and root dry mass presented a strong negative correlation to the reduction in crop grain yield. The decrease in yield reached 69% with 12 sourgrass plants m-2 when compared to control. The density of 3.7 weed plants m-2 reduced the maximum common bean grain yield by half. Such significant results suggest the need for developing efficient sourgrass management methods and strategies to avoid common bean yield loss.